Fluid Infusion Through Chest Tube to Facilitate Pleural Procedures: A Feasibility Study. Issue 3 (July 2020) - Majid, Adnan; Rivera, Estefania; Sisniega, Carlos; Husta, Brian; Chee, Alex; Parikh, Mihir; Holden, Van; Kheir, Fayez
Abstract : Background: Most pleural procedures need the presence of a moderate effusion to allow safe access to the pleural space. We propose a technique to allow safe access in patients with a drained pleural space who require further pleural evaluation or treatment during the same hospital stay. Methods: This was a retrospective study. All patients who underwent any pleural intervention with a prior infusion of fluid in the pleural space using a pre-existing chest tube (⩽14 Fr) were included. Before the pleural intervention, warm saline was infused into the pleural space through the small-bore chest tube until enough fluid was detected on thoracic ultrasound to allow pleural access. Data on patient demographics, indication for the pleural procedure, and patient outcome was analyzed. Results: A total of 22 patients with pleural disease underwent definitive pleural procedure facilitated by fluid infusion. Median volume of fluid infused was 1000 mL (850, 1500 mL). The median time between the initial chest tube insertion and the subsequent definitive pleural procedure was 3 days (2, 7 d). All procedures were completed successfully. One patient had a hemothorax secondary to fluid infusion. Conclusion: Fluid infusion through a chest tube is a feasible technique for patients that require a pleural procedure and have minimal fluid after initial pleural drainage. This approach may facilitate pleural procedures, reduce incidence of complications, and expedite the diagnosis and treatment of patients with pleural diseases. Pressure infusers should not be used during this procedure as there is a theoretical increased risk of complications.